JOM FMIPA Volume 1 No. 2 Oktober 2014 372 BIOLOGI REPRODUKSI IKAN LAIS PANJANG LAMPUNG (Kryptopterus apogon) DI SUNGAI KAMPAR KIRI DAN SUNGAI TAPUNG, PROVINSI RIAU - Reni Mirsa Sari; Roza Elvyra; Yusfiati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Fish of Lais Panjang Lampung is one of the unique fish from Pekanbaru and has high economic value but currently become endangered. This study was aimed to examine aspects of Lais panjang Lampung (Kryptopterus apogon) reproduction which include the development of gonads, gonad maturity index, sex ratio, spawning season, and spawning patterns. This study was conducted from October 2013 to March 2014 at Kampar Kiri River and Tapung. The number of fish obtained were 324 individuals with 124 males and 200 females. Total length and body weight of male and female fish ranged from 19 to 38.2 cm (31.13 to 209.06 g) and 20.5 to 33.4 cm (30.02 to 158.06 g), respectively. Sex ratios between male and female fish were 1:1,6. The males and females with TKG IV were commonly found in March (22.22%) and October (15.15%), respectively. Furthermore, the highest IKG of males and females fish were found in October, they were 0.066% and 0.5595% respectively. Fecundity of K. apogon ranged from 7294-35.742. Spawning patterns of Lais Panjang Lampung fish (Kryptopterus apogon) is a total spawner.